2022
DOI: 10.3390/life12050638
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Glutamate Neurotransmission: From Physiology to Pathophysiological Mechanisms of Retinal Ganglion Cell Degeneration

Abstract: Glutamate neurotransmission and metabolism are finely modulated by the retinal network, where the efficient processing of visual information is shaped by the differential distribution and composition of glutamate receptors and transporters. However, disturbances in glutamate homeostasis can result in glutamate excitotoxicity, a major initiating factor of common neurodegenerative diseases. Within the retina, glutamate excitotoxicity can impair visual transmission by initiating degeneration of neuronal populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 357 publications
(430 reference statements)
2
27
0
Order By: Relevance
“…This treatment protocol with ITH12657 resulted in substantial rescue of Brn3a + RGC (up to 72%) when compared to vehicle treatment (27%), and thus, such a treatment regime was implemented thereafter in the following experiments. It is well known that calcium channel blockade could influence retinal functionality and other pathways in a healthy animal ( Boccuni and Fairless, 2022 ). It is possible that our best results obtained when treatment was started 12 h prior to NMDA administration, were due to the fact that the molecule has the necessary time to reach the retina before activation of the death pathways induced by NMDA excitotoxicity, which is very fast and aggressive ( Vidal-Villegas et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…This treatment protocol with ITH12657 resulted in substantial rescue of Brn3a + RGC (up to 72%) when compared to vehicle treatment (27%), and thus, such a treatment regime was implemented thereafter in the following experiments. It is well known that calcium channel blockade could influence retinal functionality and other pathways in a healthy animal ( Boccuni and Fairless, 2022 ). It is possible that our best results obtained when treatment was started 12 h prior to NMDA administration, were due to the fact that the molecule has the necessary time to reach the retina before activation of the death pathways induced by NMDA excitotoxicity, which is very fast and aggressive ( Vidal-Villegas et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cholinergic waves propagated by starburst amacrine cells have also been implicated in the development of retinal deep plexus vessels and BRB maturation 14 . While glutamate is the predominant neurotransmitter in the retina during vascular development and in adulthood 70 , nothing is known about whether glutamatergic neuronal activities regulate retinal angiogenesis and BRB maturation. Our study elucidates this critical missing step that links glutamatergic neuronal activities with vascular development and maturation in the retina - a process that may also be relevant for several retinal disease.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, various studies have shown a connection between glaucoma, neuronal cell death, and the increased release of glutamate in the retina [ 68 ]. When compared to healthy people, glaucoma sufferers’ vitreous and retinal mounts showed elevated amounts of glutamate and glutamine (a metabolic precursor) and lower levels of the glutamate transporter excitatory amino acid transporter 1 [ 69 ]. This further confirms the role of neurotransmitters in the disease and needs to be studied well.…”
Section: Neurodegenerative Diseases Affecting the Eyementioning
confidence: 99%